Shifting the scientific paradigm for the transformation of higher education: Experience at State Islamic University (UIN) in Indonesia - Ahmad Muthohar; Abdul Ghofur; M. Mukhsin Jamil; Muhammad Sulthon (Universidad de Deusto, 2023)
Every university has many ways to make changes, and institutional transformation is one of the strategic choices to achieve excellence. However, the transformation of higher education is still dynamically defined and open. The practice also has many models and differences. This article examines the scientific paradigm shift to rethink the practice of transformation for higher education. Identifying new scientific paradigms, shifting processes, models used, practical steps, factors, and challenges is the primary concern of research work. This research was conducted qualitatively with a narrative approach. Multi-site studies at several State Islamic Universities (UIN) in Indonesia were reviewed to obtain findings about the different models applied. The results show that the transformation of higher education is simultaneously carried out by changing the institutional status and renewing the scientific paradigm. Science integration is used as a new scientific paradigm even though, in practice, each university has a different model. This new paradigm has wideranging impacts, such as eliminating scientific dichotomies that have long been practiced, expanding multidisciplinary scientific structures, and adding authority to develop faculties and study programs. Another impact is the existence of new awareness and enthusiasm for several changes in the aspects of it. Many challenges need to be anticipated to obtain better quality, such as the need for curriculum reformulation, changes in organizational behavior, a new image, and many other programs. We recommend this finding as an example of good practice in improving the quality and institutional system of higher education. To understand the wider impact of this transformation process, such as competency and graduate outcomes, changes in organizational behavior, the direction of research and community service programs, and their social impact in the future, more research on sustainability is needed. Received: 19 June 2022 Accepted: 25 September 2023